2018
DOI: 10.1590/1983-21252018v31n205rc
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Yield and Nutritional Characteristics of Sweet Pepper Grown Under Salt Stress in Hydroponic System

Abstract: Irrigation with brackish water is common in the semiarid region of the Brazilian Northeast, potentiating the process of salinization of the soil in these areas. The hydroponic system stands out as an important strategy for crop management in semiarid regions, since crops show greater tolerance to the salt stress under hydroponic conditions, which minimize the effects of soil salinization. Thus, the objective of this work was to evaluate the effects of salt stress on the growth, fruit yield and mineral nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In peppers, calcium is the third most accumulated nutrient by plants (Lima et al, 2018), and its deficiency can lead to fruit apical rot. Boron is the micronutrient most accumulated by pepper fruits and, in adequate amounts, it can favor the development and production of fruits and its deficiency can lead to floral abortion and poor seed formation (Mello et al, 2002).…”
Section: Palavras-chavementioning
confidence: 99%
“…In peppers, calcium is the third most accumulated nutrient by plants (Lima et al, 2018), and its deficiency can lead to fruit apical rot. Boron is the micronutrient most accumulated by pepper fruits and, in adequate amounts, it can favor the development and production of fruits and its deficiency can lead to floral abortion and poor seed formation (Mello et al, 2002).…”
Section: Palavras-chavementioning
confidence: 99%
“…In the plants grown in the ground with side coating of grooves and mulch, the biofertilizer promoted a reduction in the level of Chl t from 1.0 to 0.79 mg g -1 FM. This decrease may be due to the high electrical conductivity of the enriched biofertilizer (Table 4), which provides high levels of Ca 2+ , Mg 2+ , Na + and Cl - (Cavalcante et al, 2019;Oliveira et al, 2014;Sediyama et al, 2014), and the largest buildup of moisture, provided by the use of all of these techniques together, could have caused a nutritional imbalance, resulting in the absorption of some nutrients in excess, such as Na + and Cl -, which are toxic to plants (Lima et al, 2018). A similar situation was recorded by Corrêa et al (2009), who concluded that high input rates of cow and poultry manure inhibit the production of chlorophyll despite raising the levels of chlorophyll in plants.…”
Section: Leaf Chlorophyll Contentmentioning
confidence: 99%
“…Responsibility for more sustainable and rational agriculture should not be seen as additional pressure on production costs but as an economic criterion for agricultural production and preservation of the system. Some studies recently conducted worldwide have investigated efforts to evaluate the effects of salinity under hydroponic conditions, with emphasis on aspects of production and water consumption (ATZORI et al, 2019;CAPARROTTA et al, 2019;MODESTO et al, 2019;LIMA et al, 2018;SILVA et al, 2020). This evidence the direction of research to update the expectations of commercial production with the use of brackish water, based on the premise that, when the production systems evolve, the responses of plants to salinity tend to be positively altered.…”
Section: Introductionmentioning
confidence: 99%